Farmer’s Individual Potential in Different Farm Sizes of Local Beef Cattle Farming in Kebumen Regency, Indonesia - Mochamad Sugiarto; Syarifuddin Nur; Oentoeng Edy Jatmiko; Marti Ike Wahyu (Buletin Peternakan, 2018)
This study aims (1) identify the farmer’s individual potential in different farm sizes and (2) analyze the relationship of basic potential, availability of man power potential, provision of production input potential, and technological mastery potential with the increasing farm size of PO Kebumen cattle. 100 respondents (breeding farmers) from 6 sub-districts known as PO Kebumen beef cattle development centers are selected using a multistage sampling method. The results of Kruskal Wallis Test explain that farmer’s individual potential of PO Kebumen beef cattle farming showed significant difference at different farm size (P<0.01). Based on the Spearman rank correlation test, the availability of technological potential and the provision of production input potential are considered as the important elements regarding to the increasing farm size of PO Kebumen beef cattle (P <0.01). The mastery of technology and the provision of production inputs are the driving factors for increasing the farm size of PO Kebumen cattle.